2004
DOI: 10.1598/rrq.39.2.2
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the effects of intrinsic motivation, extrinsic motivation, amount of reading, and past reading achievement on text comprehension between U.S. and Chinese students

Abstract: S This study examined the extent that motivational processes facilitate the comprehension of texts and the extent of culture's role in children's motivational processes of text comprehension. Relationships between intrinsic and extrinsic motivation, the amount of reading, past reading achievement, and text comprehension were examined by utilizing structural equation modeling. Fourth‐grade students (187 U.S. and 197 Chinese) were administered a reading test and two questionnaires regarding reading motivation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

65
528
6
70

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 545 publications
(669 citation statements)
references
References 62 publications
65
528
6
70
Order By: Relevance
“…Although there is a significant body of research investigating the relationship between children's reading skills and reading motivation (Baker & Wigfield, 1999;Becker, McElvany & Kortenbruck, 2010;Morgan & Fuchs, 2007;Taboada et al, 2009;Wang & Guthrie, 2004) and also reading frequency (Echols, West, Stanovich & Zehr, 1996;Guthrie, Wigfield, Metsala & Cox, 1999), there is considerably less research with adolescents. Indeed, Conradi, Gee Jang and McKenna (2014), in a recent review of reading motivation research, found that only 8% of existing studies had been carried out among high school aged students (9 th -12 th grades).…”
Section: Running Head: Adolescent's Reading Skill Motivation and Habitsmentioning
confidence: 99%
“…Although there is a significant body of research investigating the relationship between children's reading skills and reading motivation (Baker & Wigfield, 1999;Becker, McElvany & Kortenbruck, 2010;Morgan & Fuchs, 2007;Taboada et al, 2009;Wang & Guthrie, 2004) and also reading frequency (Echols, West, Stanovich & Zehr, 1996;Guthrie, Wigfield, Metsala & Cox, 1999), there is considerably less research with adolescents. Indeed, Conradi, Gee Jang and McKenna (2014), in a recent review of reading motivation research, found that only 8% of existing studies had been carried out among high school aged students (9 th -12 th grades).…”
Section: Running Head: Adolescent's Reading Skill Motivation and Habitsmentioning
confidence: 99%
“…However, intrinsic motivation has been more strongly correlated with the amount of reading than extrinsic motivation in many studies (e.g., Becker et al, 2010;Law, 2009;Schiefele et al, 2012;Wang & Guthrie, 2004;Wigfield & Guthrie, 1997). Extrinsic motivation has been negatively associated with reading amount and/or reading comprehension in some studies (e.g., Becker et al, 2010;Law, 2009;Schiefele et al, 2012;Wang & Guthrie, 2004). To sum up, as SDT postulates (Deci & Ryan, 2000, 2002, the findings of L1 reading research confirm the superior effects of intrinsic motivation as compared to extrinsic motivation.…”
Section: Reading Motivationmentioning
confidence: 99%
“…Although the conceptualizations are slightly different, intrinsic motivation and extrinsic motivation have been employed to investigate L1 reading motivation in many studies (e.g., Becker, McElvany, & Kortenbruck, 2010;Guthrie & Wigfield, 2000;Law, 2009;Mathewson, 1979Mathewson, , 1985Schiefele, Schaffner, Möller, & Wigfield, 2012;Wang & Guthrie, 2004;Wigfield & Guthrie, 1997). In general, "both [intrinsic and extrinsic motivation] predict children's reading amount and frequency" (Guthrie & Wigfield, 2000, p. 407) in L1 reading.…”
Section: Reading Motivationmentioning
confidence: 99%
“…Mathewson (1979) also argued that although an important factor in the decision to read is the intrinsic motivation derived from reading an interesting story, a minimal degree of extrinsic motivation might also be necessary even for the reading of interesting stories, as no children read well when they were allowed to read or play with toys. However, intrinsic motivation has been more strongly correlated with the amount of reading than extrinsic motivation in many studies (e.g., Becker et al, 2010;Law, 2009;Schiefele et al, 2012;Wang & Guthrie, 2004;Wigfield & Guthrie, 1997). Extrinsic motivation has been negatively associated with reading amount and/or reading comprehension in some studies (e.g., Becker et al, 2010;Law, 2009;Schiefele et al, 2012;Wang & Guthrie, 2004).…”
Section: Reading Motivationmentioning
confidence: 99%
See 1 more Smart Citation